Novel aspect of essential oils with a history of antimicrobial activity to be used as a potential source of carbon and nitrogen for the nutrition of Candida pathogens - Suad Yousif Aldorkee; Ali Abdul Hussein Sadeq AL-Janabi (Acta Scientiarum. Biological Sciences, 2023)
Essential oils (EOs) are complex aromatic compounds with a broad range of biological activities. Those with a history of antimicrobial action were evaluated in this study as a nutritional source for pathogenic Candida. Clinical isolates of Candida spp. were cultivated on two types of media with six types of EOs (aniseed, purple nutsedge, harmal, camphor, black seed, and linseed). One medium contained only glucose (GM) and the second contained only peptone (PM). Many EOs in GM encouraged the growth of several Candida isolates. The EOs in PM showed low support to many isolates. Isolate 2 of C. albicans was the most effective strain to use with nearly every EO tested in the two media. In conclusion, EOs can be used as a source of carbon and nitrogen depending on the type of EO and fungal species. In an environment with less nutrients, EO may be recommended as a nutrient source for fungi rather than for its known antifungal activity.